Báo cáo chuyển đổi số giáo dục ở cấp tỉnh trong bối cảnh sáp nhập đơn vị hành chính: Thực trạng và vấn đề đặt ra trong công tác quản lí - Dương Thị Thảo, Dương Thị Thảo; Hoàng Thị Song Thanh, Hoàng Thị Song Thanh (Tạp chí Giáo dục, 2026)
Digital transformation in education at the provincial level plays a critical role in improving the effectiveness of educational governance, supervision, and administration. However, in the context of administrative mergers, differences in approaches and levels of standardization in digital transformation reporting across localities may affect the quality of information used for management purposes. This paper analyzes the current status of digital transformation reporting in education before and after provincial merger through a qualitative research design combining document analysis and comparative case study. The findings reveal substantial differences in report structure, data usage, and evidence presentation among localities. At the same time, the reporting model with a higher level of standardization tends to dominate the post-merger reporting system. Based on these findings, the paper proposes several solutions to improve the provincial digital transformation reporting framework in education, thereby enhancing consistency, transparency, and the overall effectiveness of educational management in the context of digital transformation.